LACUBLACUBA Lamp Innovation to Enhance Gill Net Fisheries in Central TapanuliA Lamp Innovation to Enhance Gill Net Fisheries in Central Tapanuli - Fuah, Ricky Winrison; Hutagalung, Amanda Isa Putra; Rahayu, Rosi; Muna, Zakyatul; Andhini, Nadia; Khobir, Muhammad Latiful; Fazri, Kurniawan (Departemen Teknik Kelautan Universitas Hasanuddin, 2025)
Most of the Central Tapanuli Regency area is on the coast, which is part of the Indian Ocean waters and has great potential in the fishing industry, especially marine fisheries. One of the fishing gears widely used by fishermen in Central Tapanuli is the gill net. Although the amount of marine fisheries resources in Central Tapanuli is quite abundant, the catch of salam net fishermen often fluctuates, so fishing aids are needed to increase catches, one of the efforts made is using LACUBA. This research was conducted from February to April 2024 in Sibolga Bay, Central Tapanuli. This study used a completely randomised design (CRD), with the first 30 metres of gill net treatment with LACUBA and the remaining 30 metres without LACUBA treatment with a total net length of 60 metres. The results showed that the catch of gill nets using LACUBA influenced the catch, the total catch was 16,845 grams, without LACUBA 8,290 grams for 14 times. Gill nets with LACUBA can increase catches compared to without LACUBA, due to the addition of attractants to the net, so that fish including positive phototaxis will be caught in the net, besides that fish that are looking for prey are also caught because they want to prey on their food in the gill net area.